1986
DOI: 10.1111/j.1471-4159.1986.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of High‐Affinity Choline Uptake and Acetylcholine Synthesis by Quinuclidinyl and Hemicholinium Derivatives

Abstract: Choline uptake into cholinergic neurons for acetylcholine (ACh) synthesis is by a specific, high-affinity, sodium- and temperature-dependent transport mechanism (HAChU). To assess the role of choline availability in regulation of ACh synthesis, the structure-activity relationships of several hemicholinium (HC) and quinuclidinyl analogs were evaluated in a dose response manner. As confirms previous studies, the HCs, e.g., HC-3, acetylsecohemicholinium, and HC-15 are potent inhibitors of HAChU, HC-3 being the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…19,20 Generally, quaternarization causes an increase in the inhibition of choline uptake in cholinergic neurons (regulation of acetylcholine synthesis) as has been studied with 3-quinuclidinol derivatives. 21 In the present work, a detailed fragmentation study of chemical warfare precursors is described. To our knowledge, this is the first study comprehensively covering the fragmentation pattern of these compounds using ion trap mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Generally, quaternarization causes an increase in the inhibition of choline uptake in cholinergic neurons (regulation of acetylcholine synthesis) as has been studied with 3-quinuclidinol derivatives. 21 In the present work, a detailed fragmentation study of chemical warfare precursors is described. To our knowledge, this is the first study comprehensively covering the fragmentation pattern of these compounds using ion trap mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…12 These results also suggested that 9, which also has two quaternary nitrogen atoms separated by twelve carbon atoms through two hydrophobic aromatic rings, has other constraints that dominate its improved binding to the transporter. 4 An increase in distance between the two quaternary nitrogen atoms also results in an increasing affinity for inhibition of CHT. 27…”
Section: Resultsmentioning
confidence: 99%
“…4 In order to probe selective cholinergic degradation, we have synthesized a unique series of cholinomimetic quaternary ammonium catechol-based molecules (Figure 1). 5-10 The defining structural features of this series include a quaternary ammonium group and a neighboring hydroxyl that produces a choline (Ch) analogue type affinity for cholinergic sites and a bulky, redox-active catechol moiety.…”
Section: Introductionmentioning
confidence: 99%
“…The HC3 inhibition constant for TrnCHT was estimated at 4.1 mM. Also, analogues of choline reported to be selective inhibitors of choline uptake in the mammalian cerebral cortex (IC 50 % 0:5 mM; Sterling et al, 1986) are weak inhibitors of [ 3 H]-choline uptake by TrnCHT. The experimental conditions used here to test the inhibitory ability of HC3 and quireston analogues involved exposing the TrnCHT expressing cells to [ 3 H]-choline and inhibitor simultaneously for 5 min.…”
Section: Kinetics Of [ 3 H]-choline Uptake By Insect Cells Infectedmentioning
confidence: 99%